ANALISIS KUALITAS PELAYANAN KEARSIPAN PADA BADAN ARSIP DAN PERPUSTAKAAN PROVINSI JAWA TENGAH - Hafni Lissa Nuri; Hartuti Purnaweni; Susi Sulandari (Journal of Public Policy and Management Review, 2013)
Quality of public service is very important, because the role is related to the public interest, even the interests of the people as a whole. Based on preliminary survey in Board of Archives and Library of Central Java Province, there are indications of poor quality of service. It is apparent from services performed by an employee while on duty serving the user. Users have to wait long enough to get the desired information because many officers are not in place or out official duties. The purpose of this study was to describe the quality of service archives on the Board of Archives and Library of Central Java Province.This research is descriptive quantitative study, using the five dimensions of service quality that is direct evidence (tangible), reliability (reliability), responsiveness officer (Responsiveness), employee attitudes (courtesy) and convenience (acces). The samples in this study are archival service users the Board of Archives and Library of Central Java Province, they are students, civil servants and private sector employees that amounted to 100 people taken proportional random sampling. Collecting data by spreading questionnaires to a sample containing closed questions with four answers choice. Then the research data was processed by descriptive analysis in the form of frequency distribution tables.The results showed that service quality of the Board of Archive and Library of Central Java province are included in the good category. With details that direct evidence aspect (tangible) are included in the good category, reliability aspect are included in the good category, responsiveness officer aspect are included in the good category, employee attitudes aspect (courtesy) are included in the good category and convenience aspect (acces) are included in the good category.